Differences in the effects of temperature and photoperiod on progress to flowering among diverse Mucuna spp - Qi, A.; Ellis, R.H.; Keatinge, J.D.H.; Wheeler, T.R.; Tarawali, Shirley A.; Summerfield, R.J. (Wiley, 1999)
The use of Mucuna spp. in cover crop and green manure technologies is proving to be successful in the tropics and subtropics following intensive efforts in technology transfer to farmers by NGOs (Non‐Governmental Organizations). This includes the transfer of seeds of Mucuna spp. for which the range of adaptation and the effect of environment on crop phenology are poorly understood. A selection of Mucuna spp. germplasm was evaluated over a range of contrasting photothermal conditions in controlled‐environment glasshouses. Dates of emergence and first flowering were recorded. Where possible, triple‐plane rate of development models were fitted to the first flowering data to quantify the relative sensitivity of each species to photoperiod and temperature. All accessions showed short‐day responses but there were substantial differences in the sensitivity of rate of progress to first flowering to environment, particularly to photoperiod. This results in differences in maturity period between accessions which, with appropriate understanding, could be functionally exploited by NGOs and NARS. However, if ignored, it could result in the promotion and use of accessions ill adapted to the environment in which they are tested. In consequence there might be unnecessary resistance from farmers to the adoption of green manure and cover crops technologies which are vital to the design and maintenance of sustainable farming systems in low‐income countries in the tropics.